Consistency of Hemispheric Accuracy in Inferring Sentences and Dialogs - Arifuddin, Arifuddin; Sujana, I Made (k@ta: A Biannual Publication on the Study of Language and Literature, 2010)
Broca’s and Wernicke’s discovery concerning brain language function remains debatable. The research questions: a) Is there a significant difference of accuracy among the rh, the lh, and the rh-lh in inferring auditory sentences? b) Which hemisphere shows the highest accuracy? and c) Do the rh, lh and rh-lh show consistent hemispheric accuracy when inferring sentences and short dialogs? The research results are useful for clarifying controversies against brain language function and as a foundation of ”hemispheric-based listening”. This study employed Behavioral Test with Post-test Only design. Sample involved 120 students. Data were collected through a test and analyzed with Two-way Anova. It is found that the hemispheric accuracy among the rh, lh and rh-lh in inferring auditory sentences is significantly different; the lh shows the highest accuracy in inferring auditory sentences; and the rh, lh and rh-lh show inconsistent hemispheric accuracy when inferring sentences and short dialogs.